The Mediating Role of Knowledge Management on SMEs Performance in Emerging Economies - Yonas Ferdinand Riwu; Anggi Somba Poddala; Dominikus Kopong Toni Aman; Sonia Virgarini Nawi; Chrispy Theresia Daud (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research investigates the mediating function of knowledge management in the relationship between technological innovation and the performance of small and medium-sized enterprises (SMEs) in Indonesia. The results of the analysis, which utilizes a quantitative approach and a survey of 128 SMEs, indicate that technological innovation has a positive impact on the performance of SMEs (β = 0.668; p < 0.001). Furthermore, knowledge management mediates this relationship by 63.5% (β = 0.424; p = 0.003), suggesting that the majority of the impact of technological innovation on performance is mediated by knowledge management. Investments in technology will not yield optimal returns in the absence of sufficient knowledge management capabilities. Small and medium-sized enterprises (SMEs) must effectively balance the development of knowledge management systems with the investment in technology. Also, the government must differentiate policies between developed and underdeveloped regions (3T) and enhance the knowledge management component in SME digitalization programs. By empirically demonstrating that knowledge management is a central mechanism that transforms technology into SME performance in developing countries, this study addresses a gap in the literature.